The Decision Support System in Determining Students Who Commit Violations Using Simple Additive Weighting (SAW) Method at SMA N 6 South Bengkulu - Dandi Pulama; Maryaningsih Maryaningsih; Ricky Zulfiandry (Jurnal Komputer, Informasi dan Teknologi, 2021)
School is an academic institution with the main task of providing education and developing science, technology, and art. The purpose of education is not only to develop knowledge, but also to form personality, independence, social skills, and good character. Therefore, various programs are designed and implemented to realize these educational goals, especially in the context of character building by making a school code of conduct, but it is possible for students to often violate the rules of school discipline, so a decision maker application is needed. to determine students who commit violations and will be given guidance by applying the Simple Additive Weighting (SAW) method. The application used was Visual Studio 2010 programming language and the research method used in this study is the waterfall method. The waterfall method is able to analyze the needs that are needed to find out the weaknesses of the old system, then make a design from the design and proceed with making a new system design. The result of the research is a decision support system based on the calculation data of SAW method, 30 students who commit violations will produce 3 students who get the highest violation scores so that coaching will be carried out.